Extended-spectrum beta-lactamase-producing Escherichia coli in common vampire bats Desmodus rotundus and livestock in Peru - Benavides J.A. (2018)
Antibiotic resistance mediated by bacterial production of extended-spectrum beta-lactamase (ESBL) is a global threat to public health. ESBL resistance is most commonly hospital-acquired; however, infections acquired outside of hospital settings have raised concerns over the role of livestock and wildlife in the zoonotic spread of ESBL-producing bacteria. Only limited data are available on the circulation of ESBL-producing bacteria in animals. Here, we report ESBL-producing Escherichia coli in wild common vampire bats Desmodus rotundus and livestock near Lima, Peru. Molecular analyses revealed that most of this resistance resulted from the expression of blaCTX-M-15 genes carried by plasmids, which are disseminating worldwide in hospital settings and have also been observed in healthy children of Peru. Multilocus sequence typing showed a diverse pool of E. coli strains carrying this resistance that were not always host species-specific, suggesting sharing of strains between species or infection from a common source. This study shows widespread ESBL resistance in wild and domestic animals, supporting animal communities as a potential source of resistance. Future work is needed to elucidate the role of bats in the dissemination of antibiotic-resistant strains of public health importance and to understand the origin of the observed resistance.